Phonon bottleneck in GaAs/AlxGa1−xAs quantum dots - Y. C. Chang; A. J. Robson; S. Harrison; Q. D. Zhuang; M. Hayne (AIP Advances, 2015)
We report low-temperature photoluminescence measurements on highly-uniform GaAs/AlxGa1−xAs quantum dots grown by droplet epitaxy. Recombination between confined electrons and holes bound to carbon acceptors in the dots allow us to determine the energies of the confined states in the system, as confirmed by effective mass calculations. The presence of acceptor-bound holes in the quantum dots gives rise to a striking observation of the phonon-bottleneck effect.